ASSESSMENT OF URBAN ENVIRONMENT COMFORT BY ENERGY EFFICIENCY AND ENVIRONMENTAL FACTORS IN THE CONDITIONS OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
The article provides information about the economic, geographical and ecological conditions of the Zarafshan Valley. An assessment was made of the system of removal, storage and processing of solid household and industrial waste in the settlements of Uzbekistan. To introduce a system of separate collection of solid household waste, it is necessary to change peoples behavior, to form a new attitude towards the disposal of household waste. An analysis of the problems of forming a comfortable urban environment in Uzbekistan is carried out.